2004
DOI: 10.1001/archinte.164.2.222-a
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Mortality and Long-term Use of Inhaled Corticosteroids

Abstract: I read with great interest the cross-sectional study data reported by Patil et al 1 about generalizable estimates, admission characteristics, and risk factors for in-hospital mortality in patients admitted for acute exacerbation of chronic obstructive pulmonary disease (COPD). The authors comment that age, sex, median income, comorbid illnesses, nonroutine admissions, and insurance status have a bearing on mortality during hospitalization. The relationship between long-term use of inhaled corticosteroids (ICSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Punnam et al showed that the hospital mortality of patients increased in parallel with the Deyo Modified Charlson Index score. Instead of the relationship between comorbidity number and mortality, they investigated the relationship between the comorbidity score and mortality (33). The literature has limited data on the relevant issue, and the studies investigating the effect of comorbidities on mortality in COPD generally examine the effects of diseases on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Punnam et al showed that the hospital mortality of patients increased in parallel with the Deyo Modified Charlson Index score. Instead of the relationship between comorbidity number and mortality, they investigated the relationship between the comorbidity score and mortality (33). The literature has limited data on the relevant issue, and the studies investigating the effect of comorbidities on mortality in COPD generally examine the effects of diseases on mortality.…”
Section: Discussionmentioning
confidence: 99%